Graphene oxide-based microfiber coupler for Q-switched fiber lasers - Sani, Abubakar; Mohd Yusoff, Norita; Ramli, Rizal; Hilmi Mayzan, Mohd Zul; Alresheedi, Mohammed Thamer; Md Zain, Ahmad Rifqi; Muhammad, Farah Diana; Mahdi, Mohd Adzir (Academic Press, 2026)
We demonstrate a passively Q-switched fiber laser utilizing a dual-functional device: a microfiber coupler integrated with a graphene oxide/polydimethylsiloxane composite. This composite acts simultaneously as a saturable absorber and a power splitter. This fabricated device, which utilized evanescent-wave interaction within the 5 mm fused region, exhibited a 5.25% modulation depth and an 84/16 coupling ratio. A stable Q-switched fiber laser was achieved with a pump power range of 102.15 to 177.44 mW, producing an emission at a central wavelength of 1.53 μm. The laser's pulse repetition rate was tunable from 27.78 to 54.85 kHz, with a minimum pulse width of 8.21 µs and a maximum pulse energy of 60.62 nJ. This work represents an advancement in compact and high-energy photonic devices for various practical applications.